State of Emergency: Measuring Constitutional Court Oversight - Fitriyani, Desi; Ayuni, Qurrata (Department of Constitutional Law, Faculty Sharia and Law, UIN Sunan Ampel Surabaya, 2025)
A state of emergency is an inevitable circumstance that has arisen in several regions of the world, including Indonesia. In these circumstances, there is widespread abuse of authority manifested by the excessive curtailment of rights and the violation of constitutional norms for declaring emergencies. Thus, it is necessary to have oversight from other state institutions to provide adequate checks and balances. This research aims to measure the supervision of the Indonesian Constitutional Court during a state of emergency. Normative legal research is a type of research that uses a conceptual approach, a case approach, and a comparative country approach. Through the analysis of decisions, cases, and elaboration with the principles of State Emergency Law, this paper finds that of the 3 (three) aspects of judicial supervision during a state of emergency, the aspect of supervision in the form of testing the declaration of a state of emergency is an aspect that is not owned by the Indonesian judiciary. Whereas this aspect is important, the declaration of a state of emergency issued by the President is unconstitutional.